The Impact of Currency Depreciation on Exports of SAARC Countries - Kumar, Mukesh; Begam, Azeema; Nargis (Asian Journal of Economic Modelling, 2020)
Conventionally, it is believed that decline in value of currency tends to improve exports due to relatively cheaper items making imports expensive specifically for developing economies. Hence, the aim of the study is to investigate the impact of currency depreciation on exports of SAARC countries from 1981 to 2017 using panel ARDL and ECM techniques. Correspondingly, four SAARC countries- Bangladesh, India, Pakistan, and Sri Lanka have been selected employing the data of real effective exchange rate, exports, inflation, and gross capital formation. The panel ARDL model has approved an inverse association of currency depreciation with exports in the long run and significant implication of ECM in the short run. The estimated findings have pointed towards the prevailing circumstances at both regional and country level. An inelastic nature of exportable products; lack of market diversification, confinement of domestic demand in international markets; and limited regional integration among SAARC economies are the prominent attributes of deteriorating exports. Precisely, these elements restrict the economies to bear the fruits of currency depreciation. It is concluded that SAARC economies have the potential to enhance their exports as these virtually exhibit same production patterns; and divergent comparative advantages. It is thus essential for the countries to cope up with inter and intra-regional risks and issues immediately in order to grab wider global economic prospects through enhancing exports competitiveness.